Кібербезпека хмарних обчислень та баз данних - Тертичний, В. О.; Куценко, Є. Є. (ХНУРЕ, 2020)
For any company, the most significant and valuable asset is data, since any possible data leakage can lead to the loss of critical important information, which will entail losses for the company. This means that its protection is one of the most difficult tasks facing the departments responsible for ensuring information security. The article describes methods for protecting cloud services and databases. Possible security threats in the area of cloud computing security and database protection were examined. It also considered recommendations for eliminating security threats in the field of cloud computing and also in the field of databases.